Effect of brand value announcements on stock returns: empirical evidence from Turkey - Basgoze, Pinar; Yildiz, Yilmaz; Metin Camgoz, Selin (Journal of Business Economics and Management, 2016)
This study examines the effects of brand value announcements on stock returns of Turkish firms by using the event study methodology and long-term risk adjusted port-folio returns. We examined the stock-price impacts of 299 brand value announcements on the stock market performance of the firms within the years of 2010–2014 by using BrandFinance Turkey’s 100 ranking list as a data source. The findings indicate that the companies listed in the Turkey Top 100 Brands list earn positive abnormal returns 7 months after the announcement. Similarly, the companies which had greater brand values relative to the previous year, experienced significant positive abnormal returns in the 7-months period. Additional findings suggest that investors are able to beat the market in the long run regarding risk-adjusted returns by consistently investing in the Top Brands. Overall, the study demonstrates new evidence to the marketing-finance interface by focusing on the Turkish case as an important emerging market.